Aging‐related changes in cortical mechanisms supporting postural control during base of support and optic flow manipulations. (27th October 2020) - Malcolm, Brenda R.; Foxe, John J.; Joshi, Sonja; Verghese, Joe; Mahoney, Jeannette R.; Molholm, Sophie; De Sanctis, Pierfilippo
Abstract: Behavioral findings suggest that aging alters the involvement of cortical sensorimotor mechanisms in postural control. However, corresponding accounts of the underlying neural mechanisms remain sparse, especially the extent to which these mechanisms are affected during more demanding tasks. Here, we set out to elucidate cortical correlates of altered postural stability in younger and older adults. 3D body motion tracking and high‐density electroencephalography (EEG) were measured while 14 young adults (mean age = 24 years, 43% women) and 14 older adults (mean age = 77 years, 50% women) performed a continuous balance task under four different conditions. Manipulations were applied to the base of support (either regular or tandem (heel‐to‐toe) stance) and visual input (either static visual field or dynamic optic flow). Standing in tandem, the more challenging position, resulted in increased sway for both age groups, but for the older adults, only this effect was exacerbated when combined with optic flow compared to the static visual display. These changes in stability were accompanied by neuro‐oscillatory modulations localized to midfrontal and parietal regions. A cluster of electro‐cortical sources localized to the supplementary motor area showed a large increase in theta spectral power (4–7 Hz) during tandem stance, and this modulation was much more pronounced for the younger group. Additionally, the older group displayed widespread mu (8–12 Hz) and beta (13–30 Hz) suppression as balance tasks placed more demands on postural control, especially during tandem stance. These findings may have substantial utility in identifying early cortical correlates of balance impairments in otherwise healthy older adults. Abstract : Young and older adults performed a continuous balance task in either regular or tandem (heel‐to‐toe) stance, while viewing either static visual input or optic flow. As postural demands increased, age‐specific increases in sway were accompanied by differential engagement of frontal and parietal cortices. These findings are important as they advance our understanding of cortical contributions to age‐related differences in postural control.